Potential use of the veris apparent EC sensor to predict soil texture under the semi-arid conditions of central Arizona - Oguri, Guilherme [UNESP]; Andrade-Sanchez, Pedro; Heun, John T. (My University, 2009)
The operational details of the apparent electrical conductivity (ECa) sensor manufactured by Veris Technologies have been extensively documented in literature reports, but the geographical distribution of these research studies indicate a strong regional concentration in the US Mid-west and Southern states. The agricultural lands of these states diverge significantly to the soil conditions and water regime of irrigated land in the US South-western states such as Arizona where there is no previous research reports of the use of this particular sensor. The objectives of the present study were to analyze the performance of this sensor under the conditions of typical soils in irrigated farms of Central Arizona. We tested under static conditions the performance of the sensor on three soils of contrasting texture. Observations were collected as time series data as soil moisture changed from saturation to permanent wilting point. Observations were repeated at the hours of lowest and highest temperatures. In addition, this study included soil penetration resistance and salinity determinations. Preliminary results indicate that soil temperature of the upper layer caused the most dynamic change in the sensor output. The ECa curves of the three soil textures tested had well defined distinctive characteristics. Final multivariate analysis is pending.
Keywords: Precision agriculture; Soil electrical conductivity; Soil salinity; Soil texture; Agricultural land; Apparent electrical conductivity; Arizona; AS-soils; Dynamic changes; Geographical distribution; Highest temperature; Irrigated lands; Multi variate analysis; Permanent wilting points; Precision Agriculture; Research reports; Research studies; Semi-arid conditions; Sensor output; Soil conditions; Soil penetration resistance; Soil temperature; Soil textures; Southern state; Static conditions; Time-series data; Typical soils; Upper layer; Water regime; Agriculture; Decision making; Electric conductivity; Groundwater; Multivariant analysis; Salinity measurement; Soil moisture; Textures; Time series; Sensors